2021
DOI: 10.33271/mining15.04.130
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical basis for the formation of damaging factors during the coal aerosol explosion

Abstract: Purpose. Assessing the process of damaging factors formation during the coal aerosol explosion in mine workings on the basis of theoretical research of the explosion of coal dust deposits in order to substantiate promising methods of protecting miners from their impact. Methods. An integrated approach is used, which includes a critical analysis of literature data on the occurrence and development of coal aerosol explosions in mine workings; theoretical research into the state of the gaseous medium at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Explosions in mine workings involving coal dust are characterized by the highest mortality rate in the coal mining industry. Analysis of accidents in the coal mines of Ukraine over the past decades showed that explosions of methane-air and hybrid dust-air mixtures are very common (Zavialova et al, 2021. As a result of these accidents, 1,349 miners were injured, 732 of them were fatally injured.…”
Section: Introductionmentioning
confidence: 99%
“…Explosions in mine workings involving coal dust are characterized by the highest mortality rate in the coal mining industry. Analysis of accidents in the coal mines of Ukraine over the past decades showed that explosions of methane-air and hybrid dust-air mixtures are very common (Zavialova et al, 2021. As a result of these accidents, 1,349 miners were injured, 732 of them were fatally injured.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in mining depth, the risk of each coal mine accident has increased significantly, especially the gas explosion and the fire accident [2][3][4]. When a coal mine gas explosion or fire accident happens, toxic and harmful gases such as carbon dioxide, carbon monoxide, and sulfur dioxide rapidly diffuse into the roadway [5,6]. The accident may also cause a roadway to collapse and block escape routes.…”
Section: Introductionmentioning
confidence: 99%
“…limits. Researchers [1] claim that an explosion creates a complex of unfavorable negative factors, namely high pressure, speed and temperature gas environment with highly toxic components which is formed in it and a simultaneous lack of oxygen. The relevant parameters must be known in order to prevent the combustion occurrence, to detect it and to use combustion processes for a certain technological purpose [2].…”
Section: Introductionmentioning
confidence: 99%